Interpreting Royal Discourse: Analyzing King Charles III’s Christmas Day Speech 2023 - Budiawan, Budiawan; Putra, Indra Dwi (TEKNOSASTIK, 2024)
This paper examines the interpretation of King Charles III’s Christmas Day Speech 2023,  utilizing the translation approaches proposed by Molina and Albir.  The study aims to uncover the linguistic and cultural complexities involved in interpreting royal discourse and evaluate the effectiveness of these translation strategies in this context.  Two primary objectives guide the analysis: first, to assess how Molina and Albir’s approaches enhance the interpretation’s linguistic fidelity, cultural adaptation, and communicative effectiveness;  second, to identify the challenges and strategies in translating royal speeches and the applicability of these methodologies.Through a systematic examination of the speech, the study highlights the efficacy most of the techniques, such as adaptation, calque, modulation, transposition, variation, equivalent, linguistic amplification, generalization, and literal translation.  The findings indicate that these strategies are instrumental in conveying the monarch’s intended message accurately and respectfully.  The analysis also reveals the practical challenges faced by interpreters, such as managing culturally specific references and maintaining the speech’s solemn register, and demonstrates how Molina and Albir’s approaches address the issues.  The study contributes to a deeper understanding of interpreting practices in the context of royal discourse, offering insights for interpreters, translators, and scholars alike.  It underscores the importance of strategic techniques selection to achieve both accuracy and cultural resonance. Ultimately, this research endeavors to enrich the discourse on interpreting royal speeches by offering a nuanced analysis informed by established interpreting methodologies.